Effectiveness of Various Scarification Methods on Breaking Seed Dormancy in Some Types of Palm (Arecaceae) - Setora, Ketut Weda; Wijana, Gede; Darmawati, Ida Ayu Putri (Agro Bali : Agricultural Journal, 2025)
The palm breeding and cultivation challenges are mainly related to the seed germination process. Various factors, including seed dormancy, often influence this process. Various scarification methods and several types of palms that can play a role in breaking dormancy need to be tried. This research aims to determine the best dormancy-breaking scarification method for various palm seeds. This research was carried out in Bakung Village, Sukasada District, Buleleng Regency, from January to March 2024, using a Nested Design comprising two factors. The first factor is that the type of palm seed consists of four levels: Putri palm, Pinang palm, Squirrel Tail palm, and Green palm. The second factor consists of six levels, namely control method (without peeling), peel scarification method, peel scarification method+warm water, peel scarification method+H2SO4, peel scarification method+KNO3, peel scarification method+GA3. The results of the research showed that the scarification method had a significant effect (p<0,05) on the percentage of sprouts and shoot length. Very significant effect (p<0,01) on the variables of germination, maximum growth potential, seed growth speed, and root length, had an not significant effect on the synchronization of seed growth. This research concludes that the scarification method affects breaking seed dormancy in several types of palm, except for the areca palm.